AMAZONE: prevention of persistent pain after breast cancer treatment by online cognitive behavioral therapy$dstudy protocol of a randomized controlled multicenter trial - Lukas, Anne; Theunissen, Maurice; Boer, Dianne de Korte-de; Kuijk, Sander van; Noyen, Lotte van; Magerl, Walter; Mess, Werner H.; Buhre, Wolfgang Friedrich; Peters, Madelon (Trials, 2022)
Surviving breast cancer does not necessarily mean complete recovery to a premorbid state of health. Among the multiple psychological and somatic symptoms that reduce the quality of life of breast cancer survivors, persistent pain after breast cancer treatment (PPBCT) with a prevalence of 15-65% is probably the most invalidating. Once chronic, PPBCT is difficult to treat and requires an individualized multidisciplinary approach. In the past decades, several somatic and psychological risk factors for PPBCT have been identified. Studies aiming to prevent PPBCT by reducing perioperative pain intensity have not yet shown a significant reduction of PPBCT prevalence. Only few studies have been performed to modify psychological distress around breast cancer surgery. The AMAZONE study aims to investigate the effect of online cognitive behavioral therapy (e-CBT) on the prevalence of PPBCT.
Gesehen am 08.11.2022